The Dynamics of Iran-China “New” Strategic Cooperation - Emrah Yıldırımçakar (Alternatif Politika)
Iran-China cooperation is not one-dimensional that based only on the economic interests of the two parties. It has other dimensions such as seeking new strategies to minimize the domination of the United States in Central Asia and the Middle East to ensure the efficient operation of their future political, economic, and strategic policies. In 2013, with the declaration of the Belt and Road Initiative (BRI), Iran-China cooperation increasingly became more critical for the two countries' political, national, and international interests. To this end, Iran and China have decided to sign a long-term (25 years) strategic cooperation agreement and Iran was admitted to the Shanghai Cooperation Organization (SCO) as a full member in September 2021. Since Iran and China have common interests in political, economic, security, and military cooperation, it is predicted that the strategic and long-standing cooperation between Iran and China will be one of the most significant factors to change the balance of the Middle East and Central Asia both politically and economically. From this point of view, this study aims to explore the dynamics affecting Iran-China strategic cooperation and analyze the core factors behind this rapprochement.